Evolution of acute ischemic stroke therapy from lysis to thrombectomy: Similar or different to acute myocardial infarction?. (1st November 2016) - Elgendy, Islam Y.; Mahmoud, Ahmed N.; Mansoor, Hend; Mojadidi, Mohammad K.; Bavry, Anthony A.
Abstract: Acute ischemic stroke remains a major global cause of death, permanent disability, and dementia. For nearly two decades, intravenous tissue plasminogen activator (tPA) has been the only recommended therapy, albeit administered within the recommended time window (i.e., < 4.5 h). However, intravenous tPA is associated with modest recanalization rates, with a majority of patients having poor functional outcomes despite timely administration. Endovascular therapy has recently been introduced as adjunctive management of acute ischemic stroke. First generation endovascular thrombectomy devices have failed to improve outcomes compared with intravenous tPA. However, recent randomized trials utilizing stent retrievers demonstrated that these devices improve functional outcomes in patients with acute ischemic stroke secondary to large-artery occlusion. Introduction of stent retrieves has begun a new era for acute ischemic stroke therapy. This comprehensive review discusses the evolution of acute ischemic stroke therapy over the last two decades, with emphasis on recent randomized trials evaluating stent retrievers. Additionally, similarities and differences between the evolution of therapy in ST elevation myocardial infarction and acute ischemic stroke will be highlighted. Highlights: Acute ischemic stroke is a major global cause of death, and permanent disability. Intravenous tPA has been the only recommended therapy, if given in the time window. Intravenous tPA is associated with modest recanalization rates. Catheter-based interventions in acute ischemic stroke lagged for several years. Stent retrievers emerged as the first effective new therapy in the last 20 years.